Devotion to Looka Product Innovation Throught the Putra Tunas Asri Boarding House - Rifqi, Farhan; Marlina, Selvi; Puspita, Dinda; Muhklisin, Risky; Arunita, Sefia Rahmania (Yayasan Putra Adi Dharma, 2024)
Small and medium enterprises (SME/UKM) play an important role in national economic development, because (SME/UKM) are the backbone of economic development. product development and innovation is currently important because the beverage industry is the largest industry in Indonesia. for this reason, there is a need for product development and innovation so that (SME/UKM) cam compete. the problem is that most (SME/UKM) do not apply development and innovation to their products, resulting in a decline in sales. the aim of this service is to improve and open up innovation to (SME/UKM). the activity stages carried out were developing a Looka beverage product with the basic ingredients of bigcola, mango,orange,basil seeds and gelatin to increase innovation in the beverage business throught teenagers at Kost Putra Tunas Asri.